2006
DOI: 10.2190/k441-p725-8174-55x2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Computer Self-Efficacy—An Examination of Learning Motivations and Learning Environments

Abstract: The purpose of this article is to discuss determinants of computer self-efficacy from the perspective of participant internal learning motivations and external learning environments. The former consisted of three motivations-interest, trend, and employment-while the latter comprised two environmentshome and school. Through an intermediate variable-computer use-a causal model was constructed to analyze how the determinants affected participant computer self-efficacy. To validate the model, 235 vocational and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…Consistent with prior discussions of computer-supported instruction generally (see Moos and Marroquin 2010;Thompson and Lynch 2003), findings from the present project corroborate those from studies also addressing participation that have underscored the roles of self-efficacy (Hsu and Huang 2006;Liaw et al 2007;Thompson and Lynch 2003;Thompson et al 2002), the ability to navigate (Scott and Schwartz 2007), appreciation of the relevance of content (Azevedo et al 2004), and interest (Hsu and Huang 2006;Lawless and Kulikowich 1996). The present findings also indicate that a wide-range of users will choose to engage in serious thinking about mathematics together online, and that their engagement is sustained when they feel challenged and/or have clear goals for participating.…”
Section: Study Findings and Prior Researchsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with prior discussions of computer-supported instruction generally (see Moos and Marroquin 2010;Thompson and Lynch 2003), findings from the present project corroborate those from studies also addressing participation that have underscored the roles of self-efficacy (Hsu and Huang 2006;Liaw et al 2007;Thompson and Lynch 2003;Thompson et al 2002), the ability to navigate (Scott and Schwartz 2007), appreciation of the relevance of content (Azevedo et al 2004), and interest (Hsu and Huang 2006;Lawless and Kulikowich 1996). The present findings also indicate that a wide-range of users will choose to engage in serious thinking about mathematics together online, and that their engagement is sustained when they feel challenged and/or have clear goals for participating.…”
Section: Study Findings and Prior Researchsupporting
confidence: 89%
“…Research has demonstrated that effective use of hypermedia requires self-regulation: making decisions about what and how to learn, how much time to spend, and whether or not learning has occurred (see Azevedo et al 2008). Additionally, this research has also suggested that working with computer-supported instruction requires an ability to navigate (Scott and Schwartz 2007), appreciation of the relevance of content (Azevedo et al 2004), and interest (Hsu and Huang 2006;Lawless and Kulikowich 1996).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…For the most part, studies of computer self-efficacy have limited their exploration of independent and dependent variables to factors that make sense in the training context (Deng et al, 2004). As computer usage is an important factor that influences computer self-efficacy, the most effective way to improve computer self-efficacy perception of individuals is increasing their computer usage (Hsu and Huang, 2006). In general, researchers confirm that computer self-efficacy not only determines the decisions of individuals in accepting and using the computer system, but is also a good predictor of achievements in computer-related tasks (Torkzadeh et al, 2003).…”
Section: Computer Self-efficacymentioning
confidence: 99%
“…Qutami and Abu-Jaber (1997) examined gender and the user's cognitive learning styles to self-efficacy in computer skills. Computer use and personal interest had a direct and significant effect on CSE (Hsu & Huang, 2006). Goh, Ogan, Ahuja, Herring, and Robinson (2007) looked at the relationship between CSE and mentoring as well as the gender of students and their mentors.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%